THE INFLUENCE OF LEARNING ORGANIZATIONS AND EMPLOYEE INNOVATION BEHAVIOR ON EMPLOYEE PERFORMANCE AT THE SURABAYA CITY CULTURE, YOUTH AND SPORTS AND TOURISM OFFICE WITH THE INTERVENING VARIABLE OF EMPLOYEE COMPETENCE - Dewi Nurhayati; Siti Mujanah; Achmad Yanu Alif Fianto (Transpublika Publisher, 2024)
This study examines and demonstrates the impact of Learning Organizations and Employee Innovation Behavior on Employee Performance in the Department of Culture, Youth and Sports and Tourism of the City of Surabaya. The research design employed in this study is explanatory research, which aims to explain the causes and consequences of existing problems. Path Analysis, along with two multiple linear regression analysis models and SPSS ver 17.0, was utilized to analyze the data. Furthermore, this study is classified as associative research. The findings of this study confirm that learning organizations have a positive and significant influence on employee competence. Furthermore, employee innovation behavior also has a positive and significant impact on employee competence. Moreover, learning organizations positively and significantly affect employee performance, while employee innovation behavior also has a positive and significant influence on employee performance. Additionally, employee competence is found to have a positive and significant effect on employee performance. However, employee competence does not act as a mediating variable in the relationship between learning organizations and employee performance. On the other hand, employee competence does serve as a mediating variable in the relationship between employee innovation behavior and employee performance.